Thickness Effect on the Optical Properties of PVC-Methyldopa Composite Films - Hammod, Osama Bedran (Al-Nahrain Journal of Science, 2013)
Optical properties of PVC-Methyldopa composite, prepared by using casting technique, with different thickness films have been studied. Parameters such as transmittance, reflectance, energy band gap and absorption coefficient were studied in the spectral rang (200-800) nm.